Liquidity, Leverage, and Bankruptcy Risk: Moderating Role of Firm Size in Indonesian Textile and Garment Firms - Fidela Agatha; Krisdiana Krisdiana; Agustina Agustina (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Bankruptcy risk assessment helps stakeholders identify financial vulnerabilities before operational failure occurs. Specific Background: Indonesian textile and garment companies face demand uncertainty, pressure on export values, cost volatility, and working capital constraints during the period 2020–2024. Knowledge Gap: Evidence on how firm size moderates the effects of liquidity and leverage on bankruptcy risk in this sector remains limited. Objective: This study investigates the impact of liquidity and leverage on bankruptcy risk and tests the moderating role of firm size. Methods: Data were collected from 13 textile and garment firms listed on the IDX, comprising 65 firm-year observations. Model selection and diagnostic tests were conducted, and panel regression with fixed effects and moderation was used for the analysis. Results: Liquidity was found to significantly increase the Altman Z-score and thus reduce bankruptcy risk. Leverage had no significant individual effect, but the combined effect of the two was significant. Firm size attenuated the effect of liquidity but did not significantly moderate the effect of leverage. Novelty: Firm size exerts a selective effect via the liquidity channel rather than through all financial determinants. Implications: Managers should pay particular attention to liquidity management.